Documentary review on pedagogical strategies for including people with intellectual disabilities in Colombian universities (Journal SCIENCEVOLUTION, 2024)
The purpose of this research is to conduct a documentary review of the pedagogical strategies applied to the inclusion of individuals with intellectual disabilities in universities in Colombia. The research-action methodology is framed within the pragmatic paradigm, using a mixed-methods approach and an interactive study design. It also focuses on conducting a systematic review, collecting, evaluating, and synthesizing information and scientific literature from a search in major databases such as Scopus and Web of Science. Additionally, a bibliometric equation was applied, and the data export was carried out in CSV format. For the preprocessing of the results, the Tree of Science algorithm was employed, resulting in an Excel file with 22 sheets that included relevant information for the total number of articles.As a result, the findings revealed various applied pedagogical strategies, including Universal Design for Learning (UDL), the use of assistive technologies, and curricular adaptations, highlighting the importance of continuous teacher training and psychosocial support. Therefore, it is concluded that the inclusion of students with intellectual disabilities in universities requires a combination of innovative pedagogical strategies and strong institutional commitment to ensure equitable and participatory access to education.
Keywords: Intellectual disability; Pedagogy; Inclusion; Higher education